Cystatin C as a predictor of acute renal damage after radical surgical treatment in patients with muscle-invasive bladder cancer - A. I. Tarasenko; V. N. Pavlov; I. R. Kabirov; A. V. Alekseev; M. F. Urmantsev (Исследования и практика в медицине, 2021)
Purpose of the study. To assess the clinical and prognostic significance of serum and urinary cystatin C (uCys-C and sCys-C) in patients undergoing radical cystectomy (RC) in relation to AKI.Patients and methods. In this prospective study, uCys-C and sCys-C levels were measured during the first week after undergoing RC in a heterogeneous group of patients undergoing RC (n=186), mean age 59.5±11.4 years. The observation period of the patients was 6 months. The diagnosis of AKI that developed within the first week after surgery was based on the KDIGO criteria.Results. Of the 186 examined patients, 43 developed AKI according to generally accepted criteria. During the follow-up period, no patient required renal replacement therapy. AKI patients had a longer hospital stay (22.4±22.9 versus 13.0±4.1). The sCys-C levels were significantly associated with the occurrence of AKI and CKD in the long-term postoperative period and had an area under the ROC curve of 0.76 and 0.81, respectively, for predicting severe outcomes. At an optimal cut-off value of 161.17 ng/ml, sCys-C showed a sensitivity of 65 % and a specificity of 58 % for predicting AKI. The greatest increase in the concentration of sCys-C was detected 6-12 hours after surgery, followed by a decrease in the long-term follow-up.Conclusion. Peak sCys-C levels are associated with AKI and independently predict the development of AKI in patients after RC and the onset of CKD within 6 months.